2017
DOI: 10.1038/s41598-017-16631-8
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds from Paenibacillus polymyxa KM2501-1 control Meloidogyne incognita by multiple strategies

Abstract: Plant-parasitic nematodes (PPNs) cause serious crop losses worldwide. In this study, we investigated the nematicidal factors and the modes and mechanisms of action involved in nematode control by Paenibacillus polymyxa KM2501-1. Treatment of the second-stage juveniles (J2) juveniles of PPN Meloidogyne incognita with the biological control agent KM2501-1 resulted in a mortality of 87.66% in vitro and reduced symptoms on tomato by up to 82.61% under greenhouse conditions. We isolated 11 volatile organic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 41 publications
(48 reference statements)
6
83
0
1
Order By: Relevance
“…The presence of vacuoles was previously reported in Meloidogyne incognita , known to cause root‐knot disease in plants, and B. xylophilus treated with iodoindoles . Those reports described severe morphological variations in M. incognita following treatment with oxalic acid, which showed complete destruction of internal organs, and the death of B. xylophilus caused by 5‐iodoindole was thought to be attributed to the increased vacuolisation by methuosis, as some of these compounds can destroy the nematode's physical barrier or tissues . We observed similar morphological changes in the B. xylophilus treated with spectinabilin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The presence of vacuoles was previously reported in Meloidogyne incognita , known to cause root‐knot disease in plants, and B. xylophilus treated with iodoindoles . Those reports described severe morphological variations in M. incognita following treatment with oxalic acid, which showed complete destruction of internal organs, and the death of B. xylophilus caused by 5‐iodoindole was thought to be attributed to the increased vacuolisation by methuosis, as some of these compounds can destroy the nematode's physical barrier or tissues . We observed similar morphological changes in the B. xylophilus treated with spectinabilin.…”
Section: Discussionsupporting
confidence: 87%
“…45 Those reports described severe morphological variations in M. incognita following treatment with oxalic acid, which showed complete destruction of internal organs, 46 and the death of B. xylophilus caused by 5-iodoindole was thought to be attributed to the increased vacuolisation by methuosis, as some of these compounds can destroy the nematode's physical barrier or tissues. 47 We observed similar morphological changes in the B. xylophilus treated with spectinabilin. It indicates that spectinabilin cause tissue disorganisation and vacuole formation in B. xylophilus, leading to the nematicidal activity against the B. xylophilus.…”
Section: Discussionsupporting
confidence: 71%
“…FAc has been recognized as a flavoring agent and food additive by the Joint FAO/WHO Expert Committee on Food Additives [23]. FAc is a VOC produced by several microbes or plants [24,25], and has been considered as a promising alternative to currently available nematicides because of its nematicidal, fumigant, and attractant activities against M. incognita [24]. However, the effects of FAc on the reproduction, egg hatching, feeding, and growth of nematodes and control efficiency on RKNs in the field are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms can release volatile substances in soil or other growth matrices, and the fumigation of these substances can be used to prevent and control plant diseases [24]. Cheng [25] et al found that volatile substances produced by Paenibacillus polymyxa can control RKNs in many ways. Zhai [26] et al detected seven volatile substances in the fermentation broth of Pseudomonas putida 1A00316; among them, 2-undecanone has shown a strong nematicidal activity.…”
mentioning
confidence: 99%